Nominal Controller Design Based on Decentralized Integral Controllability in the Framework of Reconfigurable Fault-Tolerant Structures - Luppi, Patricio Alfredo (2014)
A reconfigurable fault-tolerant control system typically includes a nominal controller (NC), a fault detection/diagnosis (FDD) and decision subsystem, a reconfiguration mechanism, and a reconfigurable controller (RC). Here, a systematic methodology for designing a fully decentralized NC of reduced dimension is presented, providing (i) fault-tolerant capability due to the structural flexibility and (ii) availability of redundancies for RC design. The fulfillment of a sufficient condition for decentralized integral controllability is searched to guarantee the stability while the FDD scheme is identifying the faults. A novel framework based on a genetic algorithm is developed for obtaining alternative NCs. They are screened considering quantitative measures derived from stability and performance considerations. The procedure features complexity reduction because (i) it only utilizes steady-state process information and (ii) it is independent from the controller design. The methodology is tested in the Tennessee Eastman process to demonstrate its potential against set point/disturbance changes and stuck actuator faults.